1978
DOI: 10.1038/hdy.1978.22
|View full text |Cite
|
Sign up to set email alerts
|

Non-mendelian female sterility in Drosophila melanogaster: Hereditary transmission of reactivity levels

Abstract: SUMMARYCrosses between various strains of Drosophila melanogaster may give rise to a female sterility of non-Mendelian determination. When two factors, of as yet unknown nature, are contributed by the gametes from which F, females originate, these flies may show a more or less strongly reduced fertility. The factor carried by "reactive" strains (R factor) varies considerably in its ability to reduce fertility. This characteristic was used in experiments to analyse the heredity of R. It appears to be under comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

1979
1979
2008
2008

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(25 citation statements)
references
References 12 publications
1
24
0
Order By: Relevance
“…This sterility is the result of an interaction between a chromosomal factor I and a cytoplasmic factor R (P~lisson & Picard, 1979). The R-factor is maternally inherited but in the absence of chromosomes from the reactive strain it gradually disappears (Bucheton, 1978;Bucheton & Picard, 1978;b andb). The I-factor in Drosophila melanogaster exhibits a phenomenon called 'chromosomal contamination': crossing experiments with semi-sterile females, which have received from their father a single Icarrying chromosome, show that most or all their chromosomes, formerly devoid of I-factors, have irreversibly acquired one or more I-factors (P~lisson, 1978(P~lisson, and Picard 1978(P~lisson, c and 1979.…”
Section: Discussionmentioning
confidence: 99%
“…This sterility is the result of an interaction between a chromosomal factor I and a cytoplasmic factor R (P~lisson & Picard, 1979). The R-factor is maternally inherited but in the absence of chromosomes from the reactive strain it gradually disappears (Bucheton, 1978;Bucheton & Picard, 1978;b andb). The I-factor in Drosophila melanogaster exhibits a phenomenon called 'chromosomal contamination': crossing experiments with semi-sterile females, which have received from their father a single Icarrying chromosome, show that most or all their chromosomes, formerly devoid of I-factors, have irreversibly acquired one or more I-factors (P~lisson, 1978(P~lisson, and Picard 1978(P~lisson, c and 1979.…”
Section: Discussionmentioning
confidence: 99%
“…Early in the analysis of the R-reactivity Bucheton et al (BUCHETON and PICARD 1978;BUCHETON 1979) showed that there were differences between lines and that the strength of the R-reactivity could be influenced both by the maternal age and by the external temperature. They concluded that the Rreactivity appeared to be under complex control involving both extra-chromosomal and classical nuclear inheritance.…”
Section: Xiushan Wu Department Of Genetics Stockholm University S-mentioning
confidence: 99%
“…We prefer the model in which extrachromosomal P element DNA regulates the activity of chromosomalP elements. Moreover, this simple model has potential application in an independent system of hybrid dysgenesis called the I-R system, which has many formal similarities to the P-M system (25)(26)(27)(28)(29)(30).…”
Section: Methodsmentioning
confidence: 99%